The addition of granulocyte-colony stimulating factor shifts the dose limiting toxicity and markedly increases the maximum tolerated dose and activity of the kinesin spindle protein inhibitor SB-743921 in patients with relapsed or refractory lymphoma: results of an international, multicenter phase I/II study. Issue 9 (2nd September 2015) - O'Connor, Owen A.; Gerecitano, John; Van Deventer, Henrik; Hainsworth, John; Zullo, Kelly M.; Saikali, Khalil; Seroogy, Joseph; Wolff, Andrew; Escandón, Rafael
Abstract : This was a phase I study of SB-743921 (SB-921) in patients with relapsed/refractory lymphoma. Previous studies established that neutropenia was the only dose limiting toxicity (DLT). The primary objective was to determine the DLT, maximum tolerated dose (MTD) and efficacy of SB-921 with and without granulocyte-colony stimulating factor (G-CSF). Sixty-eight patients were enrolled, 42 without G-CSF, 26 with G-CSF. In the cohort without G-CSF, SB-921 doses ranged from 2 to 7 mg/m 2, with 6 mg/m 2 being the MTD. In the cohort with G-CSF support, doses of 6–10 mg/m 2 were administered, with 9 mg/m 2 being the MTD, representing a 50% increase in dose density. Fifty-six patients were evaluable for efficacy. Four of 55 patients experienced a partial response (three in Hodgkin lymphoma and one in non-Hodgkin lymphoma, all at doses ≥ 6 mg/m 2 ); 19 patients experienced stable disease, 33 patients developed progression of disease. G-CSF shifted the DLT from neutropenia to thrombocytopenia, allowing for a 50% increase in dose density. Responses were seen at higher doses with G-CSF support.